Volition and the 'New Public': A Convergence of US and EU Judicial Approaches to Communications to the Public - Foong, Cheryl (Sweet and Maxwell, 2020)
US and EU judicial approaches to the right to communicate to the public in copyright are converging towards a common factor – the consideration of the defendant’s fault or mental state. This article highlights this under-appreciated commonality between the two jurisdictions and critically analyses the negative impact that this trend brings to the advancement of copyright’s core objectives.